Una introducción a la literatura científica - García Molina, R.; Abril, I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
We discuss the convenience of an early introduction of undergraduate students to the reading of scientific papers, mostly divulgative or historical. This can encourage them to deeper readings and to search and discover in the scientific writings new sources of learning and pleasure. The aim of this activity is twofold: mainly, to approach the students to bibliographical sources different from the traditional textbooks and, collaterally, to habituate them to get acquainted with scientific information in foreign languages (mostly English). In this manner, the students can get further knowlegde and they can also learn new points of view or different topics from those commonly discussed during a typical academic course.